Navigating challenges and enhancing effectiveness : insights from tutors on the art of tutorial delivery - Lekota, Tebogo (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2024)
This study investigated the challenges faced by tutors in delivering effective tutorial sessions and the strategies they employed to enhance the learning experience in higher education. The study employed a qualitative research approach to explore tutors' challenges and strategies in delivering effective tutorial sessions, emphasizing in-depth understanding and rich descriptive insights. The research was grounded in the interpretivism paradigm, which seeks to understand participants' experiences and perspectives within their social and educational contexts. The study utilized a case study design, focusing on a specific group of tutors to provide detailed insights into their experiences and practices in higher education tutorial delivery. The sample size comprised 28 purposefully selected tutors. Participant selection was guided by relevance to the research focus, and data collection was concluded upon reaching data saturation. Grounded in Social Constructivism and Situated Learning Theory, the researcher used semi-structured interviews to collect data from the purposefully selected participants. The data collection process was restricted by data saturation. Accordingly, reflexive thematic analysis was used to analyze data. The findings revealed that tutors encounter diverse student needs, difficulties in fostering active participation, knowledge gaps, and time constraints. To address these challenges, tutors employed strategies such as creating supportive learning environments, utilizing active learning techniques, incorporating technology, adapting to individual learning styles, and providing constructive feedback. The study concluded with the insights gathered from experienced tutors highlighting the significant challenges they face, such as accommodating diverse learning styles, addressing knowledge gaps, and managing time constraints. The recommendations for professional development, mentoring, flexible curriculum design, and regular feedback mechanisms, are aimed at enhancing the effectiveness of tutorial delivery and ultimately improving student learning outcomes in higher education. By implementing these recommendations, educational institutions can enhance the effectiveness of tutorial delivery, ultimately leading to improved student engagement, academic success, and a richer learning experience in higher education.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 8, 2024
Keywords: Tutorial delivery; Tutors; Challenges in higher education; Student engagement; Active learning; Professional development; Technology integration; Tutors and tutoring; Active learning; Student-centered learning; Career development; Education, Higher